PERANCANGAN KONTROLER PI PLUS RANGKAIAN RESONANSI UNTUK PENEKANAN RIPPLE PADA ARUS DC MOTOR TRAKSI KERETA CEPAT DENGAN METODE SYMMETRICAL OPTIMUM - Vicky Pramana Putra; Mochammad Rusli; Muhammad Aziz Muslim (Jurnal Mahasiswa TEUB, 2023)
This research discusses the Proportional-Integral-Resonant (PIR) control system used to regulate a three-phase induction motor, ensuring stability of the speed output and reducing ripple in the DC current output. The study also covers the modulation techniques employed to control the switching of the rectifier using the Space Vector Pulse-Width Modulation (SVPWM) method, where the threephase current and voltage are represented in synchronous rotating coordinates. In this control strategy, a vector control with SVPWM modulation technique is utilized to achieve optimal DC voltage output. To obtain an optimal controller design, parameter gain tuning is performed on the speed, flux, and torque control cascade using the symmetrical optimum method. Simulation testing is carried out using MATLAB/Simulink software to demonstrate the stability of the speed output and the DC current output of the three-phase induction motor. The three-phase induction motor with the PIR controller yields better results compared to the PI controller, achieving a speed of 163.2 rad/s, reaching a steadystate condition within 0.317 seconds, exhibiting overshoot, and a steady-state error of 2.39%. Keywords: Three phase induction motor, PIR controller, Direct Torque Control, symmetrical optimum.